Metabolic benefits of changing sedentary lifestyles in nonalcoholic fatty liver disease: a meta-analysis of randomized controlled trials. (September 2022) - Ma, Qianqian; Ye, Junzhao; Shao, Congxiang; Lin, Yansong; Wu, Tingfeng; Zhong, Bihui
This study seeks to evaluate the effects of a reversal of sedentary lifestyles on the improvement of metabolic profiles in patients with NAFLD. The PubMed, Cochrane Library, Web of Science, and CNKI databases were searched up to May 15, 2021. Ten randomized controlled trials on changes in the sedentary lifestyle of patients with NAFLD were included in the analysis. Data from self-controlled case arms of randomized controlled trials investigating sedentary lifestyle alterations were extracted, and the effect size was reported as the MD and 95% CI. A total of 455 participants in 10 studies met the selection criteria. The results showed that changing a sedentary lifestyle can significantly improve ALT [MD = 4.35 (U/L), 95% CI: 0.53, 8.17], CHOL [MD = 0.31 (mmol/L), 95% CI: 0.19, 0.43], TG [MD = 0.22 (mmol/L), 95% CI: 0.10 0.34], LDL-C [MD = 0.30 (mmol/L), 95% CI: 0.02, 0.57], fasting blood glucose [MD = 0.17 (mmol/L), 95% CI: 0.03, 0.31], insulin [MD = 3.23 (pmol/L), 95% CI: 1.37 5.08], and HOMA-IR levels (MD = 0.39, 95% CI: 0.15, 0.63). Changing sedentary lifestyle can also significantly improve body mass index (BMI) [MD = 1.12 (kg/m 2 ), 95% CI: 0.66, 0.58], body fat (%) [MD = 0.34 (%), 95% CI: 0.13, 0.55] and VO2peak levels [MD = −4.00 (mL/kg/min), 95% CI: −5.93, −2.06]. No differences in AST or GGT were noted before or after lifestyle changes. Altering a sedentary lifestyle to a lifestyle with regular exercise can slightly improve the levels of liver enzymes, blood lipids, blood glucose, insulin resistance, and body mass index in NAFLD patients.